Objectively measured physical activity and C‐reactive protein: National Health and Nutrition Examination Survey 2003–2004. Issue 2 (3rd August 2011) - Loprinzi, P.; Cardinal, B.; Crespo, C.; Brodowicz, G.; Andersen, R.; Sullivan, E.; Smit, E.
<x xml:space="preserve">Abstract</x> The association between physical activity (PA) and C‐reactive protein (CRP) is inconsistent, with nearly all studies using self‐report measures of PA. The purpose of this study was to examine the association between objectively measured PA and CRP in US adults and children. Adults (N=2912) and children (N=1643) with valid accelerometer data and CRP data were included in the analyses. Logistic regression analysis was used to assess the odds of meeting PA guidelines across CRP quartiles for children and among adults with low, average, and high CRP levels. For adults, after adjustments for age, gender, race, body mass index, smoking, diabetes, and high‐density lipoprotein cholesterol (HDL‐C), compared with those with low CRP levels, odds ratios were 0.59 (CI=0.45–0.77) and 0.46 (CI=0.28–0.76) for participants with average and high CRP levels, respectively. For children, after adjustments for age, gender, race, weight status, and HDL‐C, compared with those in CRP quartile 1, odds ratios were 0.96 (CI=0.5–1.84), 1.23 (CI=0.71–2.12), and 0.79 (CI=0.33–1.88) for participants in quartiles 2, 3, and 4, respectively. Objectively measured PA is inversely associated with CRP in adults, with PA not related to CRP in children.